Zoos and animal rights : the ethics of keeping animals - Bostock, Stephen St. C., 1940- (Routledge, 1993)
A controversial and timely book which explores the long history of zoos as well as the diverse ethica l and technical issues involved. Anyone concerned with humanity's relationship with other animals will find this an inspiring and rewarding book.
Keywords: Zoo animals.; Zoos -- Philosophy.; Animal welfare.; Animal rights.; Animal Rights; Animal Welfare; Animals, Zoo; Ethics; Animaux de jardin zoologique.; Jardins zoologiques -- Philosophie.; Animaux -- Protection.; Animaux -- Droits.; NATURE -- Animal Rights.; Animal rights; Animal welfare; Zoo animals; Zoos -- Philosophy; Dierentuinen.; Rechten van het dier.; Ethiek.